Manfaat Kemangi Sebagai Bahan Alami Pengusir Nyamuk - Suwandi Suwandi; Dita Widia Agustin; Ivana Vianca; Sumiati Sumiati; Kelvin Fernando; David L Samosir; Jackie Jackie; Zariyanita Seftiana Tasya Syafira; Yustika Irawaty Simbolon (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
The main purpose of the SePORA program is to assist the citizens of Kampung Melayu to solve the problem of mosquito attacks because it can interfere with citizens’ activities, also provide different solutions and invite the citizens to be more careful about cleanliness. The benefit of SePORA program is to increase the citizens of Kampung Melayu awareness of the cleanliness of the surrounding environment by not littering. Basil leaves or Kemangi is one of the many plants that are not liked by mosquitoes. For the implementation, the method starts from the observation stage which is done 2 times to find out what the obstacles experienced by citizens of Kampung Melayu. The content of the basil leaves can disrupt the respiratory tract in mosquitoes in a short time. Using drugs that have been mixed with chemicals is dangerous, especially if used in the long run. This is the topic of our discussion. In the Kampung Melayu area is a village located on the coast. In addition to sweltering weather, this also became one of the causes of the many mosquitoes attacking which made the residents uneasy.